The Role of Libraries in Facilitating Effective Governance in Contemporary Nigerian Democracy - Udensi, Julie; Akor, Philip U. (MiddleBelt Journal of Library and Information Science, 2013)
This paper sets to find out the role of libraries in facilitating effective governance in the contemporary Nigerian democracy. To achieve this, the paper described the various library materials and services and their potentials in ensuring effective governance relating to government functionaries in Nigeria. The paper also perceives that the problem with ineffective Nigerian governments is mostly related to poor information utilization among the government functionaries. The paper therefore advocates that resources utilization and services are the sure strategies that could be used in ensuring effective governance in Nigeria.